EFFECT OF MODIC CHANGE ON CLINICAL OUTCOME OF CERVICAL DISC HERNIATION PATIENTS UNDERGOING ANTERIOR CERVICAL DISCECTOMY AND FUSION - Wibowo, Caesaroy Afif; Sri Andreani Utomo; Muhammad Faris; Tsabita Hadid (Universitas Airlangga, Surabaya, Indonesia, 2023)
Highlights The presence of preoperative Modic changes tends not to affect clinical outcomes after ACDF due to degenerative pathology, including disc herniation. Preoperative Modic changes are correlated with a worse preoperative picture. Abstract Background: Modic Change (MC) is a phenomenon that can be found in Magnetic Resonance Imaging (MRI) of patients with degenerative spinal diseases and in the cervical region. The effect of Modic change on the clinical outcome of postoperative patients has not been fully established. Anterior Cervical Discectomy and Fusion (ACDF) is a procedure that has become the gold standard in treating cervical disc herniation because it is able to eliminate pathological lesions and prevent the recurrence of nerve compression. Objective: This study aimed to determine the effect of MC on the clinical outcome of patients undergoing ACDF therapy due to degenerative disc pathology, including cervical disc herniation. Material and Method: This was a systematic review using filtered literature based on PICOs. The variables examined in this study were